Targeting acid ceramidase enhances antitumor immune response in colorectal cancer - Yadu Vijayan; Shirley James; Arun Viswanathan; Jayasekharan S Aparna; Anu Bindu; Narayanan N Namitha; Devasena Anantharaman; Manendra Babu Lankadasari; Kuzhuvelil B Harikumar (Journal of Advanced Research)
Introduction: Acid ceramidase (hereafter referred as ASAH1) is an enzyme in sphingolipid metabolism that converts pro-survival ceramide into sphingosine. ASAH1 has been shown to be overexpressed in certain cancers. However, the role of ASAH1 in colorectal cancer still remain elusive. Objective: The present study is aimed to understand how ASAH1 regulates colorectal cancer (CRC) progression and resistance to checkpoint inhibitor therapy. Methods: Both pharmacological and genetic silencing of ASAH1 was used in the study. In vitro experiments were done on human and mouse CRC cell lines. The in vivo studies were conducted in NOD-SCID and BALB/c mice models. The combination of ASAH1 inhibitor and checkpoint inhibitor was tested using a syngeneic tumor model of CRC. Transcriptomic and metabolomic analyses were done to understand the effect of ASAH1 silencing. Results: ASAH1 is overexpressed in human CRC cases, and silencing the expression resulted in the induction of immunological cell death (ICD) and mitochondrial stress. The ASAH1 inhibitor (LCL-521), either as monotherapy or in combination with an anti-PD-1 antibody, resulted in reduction of tumors and, through induction of type I and II interferon response, activation of M1 macrophages and T cells, leading to enhanced infiltration of cytotoxic T cells. Our findings supported that the combination of LCL-521 and ICIs, which enhances the antitumor responses, and ASAH1 can be a druggable target in CRC.